Association of Rhesus Males with a Langur Group - Bhatnagar, P. S.; Mathur, R. (Indian Forester, 2000)
A rare and prolonged intergeneric association between Rhesus and Langur was observed at Ambagarh Reserve Forest, Jaipur, Northern India. Behavioural observations include grooming of Rhesus males by Langur female and vice-versa and mounting Langur female by Rhesus males. This interaction appears to have a cost-benefit aspect. Advantages to Langur and Rhesus were: assistance to Langurs by Rhesus in crisis situations and benefits of living with a social group to Rhesus. The likely costs to Langurs included stress due to aggression of Rhesus and reduced access to places of shelter and food. Rhesus had the loss in opportunity to interact and mate with a diverse range of conspecifics and stress along with possible brisk of injury and mortality while interacting with dogs and Langurs.